2018
DOI: 10.1097/ajp.0000000000000561
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Posttraumatic Stress Disorder and Chronic Pain in People Seeking Treatment for Chronic Pain

Abstract: Objectives: The symptoms of Posttraumatic Stress Disorder (PTSD) and chronic pain are thought to interact to increase the severity and impact of both conditions, but the mechanisms by which they interact remain unclear. This study examines the relationship between PTSD and chronic pain and whether indices of psychological flexibility mediate the relationship between these two conditions.Methods: Standardized self-report measures of PTSD, pain severity, pain interference, depression, and psychological flexibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 76 publications
0
12
0
3
Order By: Relevance
“…Psychological flexibility has been described as a fundamental aspect of human health, involving the capacity to shift one's mindset and behaviours, in concert with one's values, to adapt to varying situational demands, including symptoms of various medical and psychiatric conditions (Kashdan & Rottenberg, ). As noted in the introduction, in previous studies, we found that the relationship between PTSD and pain at pre‐treatment was mediated by psychological flexibility, and that pain‐related outcomes in CBT for chronic pain were mediated by changes in acceptance of pain (Åkerblom et al, , ).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Psychological flexibility has been described as a fundamental aspect of human health, involving the capacity to shift one's mindset and behaviours, in concert with one's values, to adapt to varying situational demands, including symptoms of various medical and psychiatric conditions (Kashdan & Rottenberg, ). As noted in the introduction, in previous studies, we found that the relationship between PTSD and pain at pre‐treatment was mediated by psychological flexibility, and that pain‐related outcomes in CBT for chronic pain were mediated by changes in acceptance of pain (Åkerblom et al, , ).…”
Section: Discussionmentioning
confidence: 51%
“…In a previous study, we found that changes in psychological flexibility as indexed by pain acceptance, as well as changes in life control, mediated changes in treatment outcomes in individuals undergoing CBT for chronic pain at a specialist pain clinic (Åkerblom, Perrin, Rivano Fischer, & McCracken, ). In a separate study from the same pain clinic, we found that processes from the psychological flexibility model (pain acceptance, committed action, cognitive fusion) mediated the relationship between PTSD and pain‐related functioning at pre‐treatment (Åkerblom, Perrin, Rivano Fischer, & McCracken, ). These results raise the possibility that if participation in a CBT program for chronic pain also yields reductions in comorbid conditions like PTSD, depression and anxiety, these may be associated with increases in psychological flexibility or related processes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, catastrophizing and kinesiophobia have been found to predict pain-related disability (Guimarra et al, 2017), and PTSD is a more potent risk factor for developing pain than the experience of trauma in itself (Jenewein et al, 2009;Ciccone et al, 2005). Painrelated avoidance, fear-avoidance and pain catastrophizing have been found to mediate the relationship between chronic pain and PTSD (Åkerblom et al, 2018;Andersen et al, 2016). Moreover, Siqveland et al (2017) found that chronic pain was mediated by PTSD and whether the trauma was inten-tional.…”
Section: Empirical Studies On Cppc In Other Contextsmentioning
confidence: 99%
“…A dor, em geral, pode causar depressão e os sintomas de dor crônica podem ser agravados por sua presença 95 . Fatores como percepção de controle da dor, sentimento de incapacidade em lidar com a dor, incapacidade funcional, comprometimento cognitivo e tabagismo são preditores da depressão em idosos 96 .…”
Section: Dor Crônica No Idoso E Depressãounclassified